Investir de nouveaux territoires à l’adolescence - Julie Deville (Sociétés et Jeunesses en Difficulté)
The place of residence, often depending on the social position, induces a specific social experience. But if a part of the young people living in public housing districts tends to consider their neighborhood as a territory, many of them withdraw from it or go beyond its limits. Moreover, their practices will change with age and experience. This paper deals with the progressive entering of teenagers in new territories where they may feel legitimate or not, according to circumstances and to their own trajectory. School life, peers’ group and juvenile activities, family and gender intervene in this rebuilding of the relationship with territory. This dynamic relationship with territory is displayed through a research on adolescents between 15 and 20. For them, the neighborhood is an anchoring, but it is nevertheless hard for girls to build their place there. School and leisure offer opportunities to go through other urban spaces, but access to the city is often limited to commercial areas. This is as much due to a lack of willing of some young people to venture farther as to their apprehension of being considered as intruders.